The peroxisomal AAA-ATPase Pex1/Pex6 unfolds substrates by processive threading - Brooke M. Gardner (Nature Portfolio, 2018)
Pex1 and Pex6 form a heterohexameric Type-2 AAA-ATPase motor whose function in peroxisomal matrix-protein import is still debated. Here, the authors combine structural, biochemical, and cell-biological approaches to show that Pex1/Pex6 is a protein unfoldase, which supports a role in mechanical unfolding of peroxin proteins.